Factors Influencing Breast Cancer Awareness in Rural Southwest China: A Cross-Sectional Study - Zhu L; Zhou Q; Huang Z; Yang Y; Yang Y; Du Y; Zhao Y; Yu X; Li T; Chen W (Dove Medical Press, 2024)
Lingling Zhu,1,2 Qiang Zhou,1,2 Ziyue Huang,3 Yuan Yang,4,5 Ying Yang,6 Yao Du,6 Yuqian Zhao,2 Xiaoping Yu,7 Tingyuan Li,2 Wen Chen5 1College of Public Health, Chengdu Medical College, Chengdu, Sichuan, 610500, People's Republic of China; 2Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, Affiliated Cancer Hospital of University of Electronic Science and Technology of China, Chengdu, Sichuan, 610041, People's Republic of China; 3Mianyang Maternal and Child Health Care Hospital, Mianyang, Sichuan, 621000, People's Republic of China; 4School of Public Health, Xiamen University, Xiamen, Fujian, 361102, People's Republic of China; 5Department of Cancer Epidemiology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100021, People's Republic of China; 6Yanting County Maternal and Child Health Hospital, Mianyang, Sichuan, 621600, People's Republic of China; 7School of Preclinical Medicine, Chengdu University, Chengdu, Sichuan, 610106, People's Republic of ChinaCorrespondence: Xiaoping Yu, School of Preclinical Medicine, Chengdu University, Chengdu, Sichuan, 610106, People's Republic of China, Tel +86 13981909673, Email yuxiaoping@cdu.edu.cn Tingyuan Li, Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, Affiliated Cancer Hospital of University of Electronic Science and Technology of China, Chengdu, Sichuan, 610041, People's Republic of China, Tel +86 28 85420667, Email ltyuan008@126.comBackground: This study aimed to explore the current knowledge level of breast cancer among rural women in Southwest China and analyze the influencing factors of breast cancer cognition.Methods: From May to November 2022, 1468 rural women were invited to participate in this study. Demographic information and the Chinese version of the Breast Cancer Awareness Measure (C-BCAM) were collected through one-on-one investigations. The data were analyzed using descriptive statistics, chi-square tests, and multiple regression analysis in SPSS 26.0.Results: The study included a total of 1468 rural women with a median age of 54.0 (IQR, 47.0, 60.0).The average score of breast cancer in the study population was 73.0 (IQR, 66.0, 82.0). Among women in Southwest China, the awareness rates of knowledge on breast cancer symptoms, barriers to seeking medical help, and risk factors were 68.8%, 98.4%, and 62.1%, respectively. The awareness rate was found to increase with higher education levels (P< 0.001) and decrease with increasing age (P< 0.001). Multivariate logistic regression analysis identified three variables that might influence breast cancer awareness: education level, contraceptive measures, and history of breast disease (all P< 0.05). Specifically, history of breast disease (Odds ratio (OR) = 1.907, 95% CI = 1.128 ~ 3.223), middle school education (OR = 2.155, 95% CI = 1.585 ~ 2.928), and junior college education and above (OR = 5.536, 95% CI = 1.898 ~ 16.148) were positive factors for women's breast cancer awareness. Conversely, the use of intrauterine devices (OR = 0.523, 95% CI = 0.384 ~ 0.712) was found to be a negative factor for women's breast cancer awareness.Conclusion: This study highlights the insufficient awareness of breast cancer among women in rural area of Southwest China. It emphasizes the necessity of health education to improve female breast cancer awareness.Keywords: China, breast cancer, awareness, screening, rural women